Authors (The Biblical archaeology review, 2025)
Susan Ackerman (Women and Prophecy in Biblical Israel) is a retired professor of religion and women’s and gender studies at Dartmouth College. She specializes in women and the religion of ancient Israel. Zeba Crook (Book Review: The Quest for John the Baptist) is Professor of Religion at Carleton University in Ottawa, Canada. He focuses on […]